Chicken breast-derived alcohol dehydrogenase-activating peptides in response to physicochemical changes and digestion simulation: The vital role of hydrophobicity. (October 2020) - Xiao, Chuqiao; Zhou, Feibai; Zheng, Lin; Cai, Yongjian; Su, Guowan; Luo, Donghui; Zhao, Mouming
Graphical abstract: Highlights: CBMHs showed a wide range of stability to meet conditions in food processing. CBMHs was insensitive to pepsin but could be digested by pancreatin. The loss activity of CBMHs may result from degraded hydrophobic peptides. Hydrophobic peptide-ADH interaction may contribute to ADH activation. Abstract: Chicken breast muscle hydrolysates (CBMHs) could promisingly activate alcohol dehydrogenase (ADH) and ameliorate alcohol-induced liver injury. The aim of this work was to investigate the stability of CBMHs against physicochemical treatments and gastrointestinal digestion simulation. Results indicated that CBMHs showed good stability towards heating (25–121 °C), pH treatment (pH 2–12) and remained stable in the presence of NaCl (0.01–2 M) and low concentration of metal ions (0.1 mM Zn 2+, Ca 2+, Fe 2+, and Fe 3+ ). Results from in vitro digestion implied a retained activity of CBMHs after gastric tract, but marked decrease (33.42%) after intestinal tract. UPLC-ESI-Q-ToF-MS/MS analysis together with in silico assessments then revealed that the degradation of hydrophobic peptides (i.e., VAPEEHPTLL, YPGIADRM, ADGPLKGIL, and KDLFDPVIQ) during simulated intestinal digestion may be account for the decreased activity. Conformational changes of ADH upon hydrophobic interaction with synthetic peptides were further confirmed by fluorescence quenching study, possibly responsible for the enhanced ADH activity. Hence, CBMHs noticeably showed good stability against physicochemical treatments and digestion simulation, while attempt establishing the structure–activity relationship of peptides is also fundamental before applying CBMHs as functional ingredient.